An integrated genomic and biochemical approach to investigate the potentiality of heirloom tomatoes: Breeding resources for food quality and sustainable agriculture - Tripodi, Pasquale; D’Alessandro, Antonietta; Francese, Gianluca (Frontiers in Plant Science, 2023)
A revival of interest in traditional varieties reflects the change in consumer preferences and the greater awareness of the quality of locally grown products. As ancient cultivars, heirlooms have been selected for decades in specific habitats and represent nowadays potential germplasm sources to consider for breeding high-quality products and for cultivation in sustainable agriculture. In this study, 60 heirloom tomato (S. lycopersicum L.) accessions, including diverse varietal types (beefsteak, globe, oxheart, plum, and cherry) were profiled over two seasons for the main chemical and biochemical fruit traits. A medium-high level of heritability was found for all traits ranging from 0.52 for soluble solids to 0.99 for fruit weight. The average content of ascorbic acid was ~31 mg 100g−1 of fw in both seasons, while greatest variability was found for carotenoids with peaks of 245.65 μg g−1 of fw for total lycopene and 32.29 μg g−1 of fw for -carotene. Dissection of genotypic (G) and seasonal (Y) factors highlighted the genotype as the main source of variation for all traits. No significant effect of Y and G × Y was found for ascorbic acid and fruit weight, respectively, whereas a high influence of Y was found on the variation of lycopene. Molecular fingerprinting was performed using the 10K SolCAP array, yielding a total of a 7,591 SNPs. Population structure, phylogenetic relationships, and principal components analysis highlighted a differentiation of plum and cherry genotypes with respect to the beefsteak and globe types. These results were confirmed by multivariate analysis of phenotypic traits, shedding light on how breeding and selection focused on fruit characteristics have influenced the genetic and phenotypic makeup of heirlooms. Marker traits association showed 11 significantly associated loci for -carotene and fruit weight. For -carotene, a single variant on chromosome 8 was found at 12 kb to CCD8, a cleavage dioxygenase playing a key role in the biosynthesis of apocarotenoids. For fruit weight, single association was located at less than 3 Mbp from SLSUN31 and fw11.3, two candidates involved in the increasing of fruit mass. These results highlight the potentiality of heirlooms for genetic improvement and for candidate gene identification.